Navigating Previvorship: Exploring the Barriers and Motivators to Lifestyle Behaviour Change in Women with BRCA Pathogenic Gene Variants - Crowley, Orla (Trinity College Dublin. School of Medicine. Discipline of Physiotherapy, 2026)
Background: Pathogenic variants in the BRCA1 and BRCA2 genes dramatically elevate a woman's lifetime risk of breast and ovarian cancer. While clinical strategies such as genetic counselling and prophylactic surgery are well established, growing attention is being placed on modifiable lifestyle factors that may support cancer prevention and overall well-being. However, the specific challenges and motivations for adopting healthy behaviours in this genetically high-risk group remain underexplored. Aims: This thesis investigates the landscape of lifestyle interventions for women with BRCA pathogenic gene variants and seeks to understand their lived experiences, motivations and barriers to behavioural change. Methods: This research used a sequential qualitative design approach informed by a scoping review. The first study, a scoping review, identified and characterised existing lifestyle interventions for women at high risk of breast cancer, predominantly due to a BRCA1/2 pathogenic gene variant, and examined findings in consideration of the COM-B model (Capability, Opportunity, Motivation, Behaviour) of health behaviour change. Building on this, the second study, a qualitative project, was completed, which utilised focus groups and didactic interviews to explore the behavioural determinants from the perspectives of women with BRCA1/2 pathogenic gene variants. Results: The review revealed that multicomponent interventions targeting physical capability and opportunity, via home-based and digital platforms, show potential for promoting health behaviour change with studies reporting high adherence rates (above 80%). However, the qualitative insights painted a more complex picture. The findings revealed that while women often have strong intentions to modify their lifestyle, emotional exhaustion and information overload, particularly from medical appointments, act as significant barriers. Participants described significant informational gaps, a lack of BRCA-specific resources and a unique psychological landscape shaped by `previvorship', the emotional tension between proactive control and the inevitability of genetic risk. Barriers related to motivation and psychological capability emerged as particularly influential. Conclusion: This research demonstrates that promoting health behaviour change in women with BRCA1/2 pathogenic gene variants is a complex process influenced by a nuanced interplay of capability, opportunity and motivation. Future interventions must be psychologically attuned, socially grounded and co-designed with patients to address their distinct emotional and motivational needs. This thesis offers a blueprint for future intervention design that foster sustainable behaviour change and holistic well-being.
APPROVED
Keywords: BRCA Pathogenic Variants; Lifestyle Behaviour Change; Hereditary Cancer Syndromes; Health Promotion; Barriers and Facilitators; Previvorship